The rise in cases of mucormycosis, candidiasis and aspergillosis amidst COVID19. (December 2021) - Ghosh, Asmita; Sarkar, Anusua; Paul, Pubali; Patel, Parth
Abstract: The Coronavirus outbreak globally has changed the medical system and also led to a shortage of medical facilities in both developing and underdeveloped countries. The COVID19 disease, being novel in nature along with high infectivity and frequent mutational rate, has been termed to be fatal across the globe. The advent of infection by SARS-CoV-2 has brought a myriad of secondary complications and comorbidities resulting in additional challenges to the health care system induced by novel therapeutic procedures. The emerging variant with respect to the Indian subcontinent and the associated genetic mutations have worsened the situation at hand. Proper clinical management along with epidemiological studies and clinical presentations in scientific studies and trials is necessary in order to combat the simultaneous waves of emerging strains. This article summarizes three of the major fungal outbreaks in India namely mucormycosis, candidiasis and aspergillosis, and elaborates their subtypes, pathogenesis, symptoms and treatment and detection techniques. A detail of future therapeutics under consideration are also elaborated along with a general hypothesis on how COVID19 is related to immunological advances leading to major widespread fungal infection in the country. The factors that contribute in promoting virus proliferation and invasive fungal infections include cell-mediated immunity, associated immunocompromised conditions and treatment protocols that slows down immune mechanisms. To better comprehend a fungal or bacterial outbreak, it is very important to conduct audits mediated through multicenter national and state research teams for recognizing patterns and studying current cases of fungal infection in both healthy and comorbid groups of COVID19 patients.